2010
DOI: 10.1002/marc.200900863
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell–Corona Micelle Stabilized by Reversible Cross‐Linkage for Intracellular Drug Delivery

Abstract: Reversibly cross-linked core-shell-corona micelles based on a triblock copolymer composed of poly(aliphatic ester), polyphosphoester, and poly(ethylene glycol) are reported. The triblock copolymer is synthesized through consecutive ring-opening polymerization of ε-caprolactone and 2,4-dinitrophenylthioethyl ethylene phosphate, followed by conjugation of poly(ethylene glycol). After deprotection under mild conditions, the amphiphilic polymer forms core-shell-corona micelles with free thiols in the shell. Cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 21 publications
1
74
0
1
Order By: Relevance
“…It is conceivable that paclitaxel-loaded Plu-SH micelles are passively targeted to the tumor tissue through the enhanced permeation and retention (EPR) effect. [39] The results show the quick release of paclitaxel from the Plu-SH micelles in an excess of DTT, similar to the GSH concentration present in cancer cells and the stability at plasma GSH levels. [40] This study demonstrates that Plu-SH nanoparticles, as carriers for paclitaxel, can be developed for efficient delivery into cancer cells.…”
Section: Paclitaxel-release Profile From the Thiolated Pluronic Micellesmentioning
confidence: 60%
“…It is conceivable that paclitaxel-loaded Plu-SH micelles are passively targeted to the tumor tissue through the enhanced permeation and retention (EPR) effect. [39] The results show the quick release of paclitaxel from the Plu-SH micelles in an excess of DTT, similar to the GSH concentration present in cancer cells and the stability at plasma GSH levels. [40] This study demonstrates that Plu-SH nanoparticles, as carriers for paclitaxel, can be developed for efficient delivery into cancer cells.…”
Section: Paclitaxel-release Profile From the Thiolated Pluronic Micellesmentioning
confidence: 60%
“…The shell cross-linked micelles lead to formation of stable nanosized hollow particles by removal of the cores after cross-linking and then hydrophilic drugs can be encapsulated inside [216,217]. Hence, reversibly shell cross-linked micelles based on triblock copolymer composed of poly(aliphatic ester), polyphosphoester, and PEG demonstrating improved physical stability were reported [218].…”
Section: Stability Of Polymeric Micellesmentioning
confidence: 99%
“…Thus, polymers containing disulfide bonds can be considered as thiol-as well as redox-responsive. Wang et al recently reported synthesis of reversibly cross-linked triblock copolymer PCL-b-poly(2,4-dinitrophenylthioethyl ethylene phosphate)-b-PEG [218]. After deprotection, core-shell-corona micelles were formed in aqueous milieu from the resultant triblock copolymer bearing thiol groups.…”
Section: Pipaam Derivativesmentioning
confidence: 99%
“…Xu et al found that SCL micelles based on PEG-b-PCL diblock copolymer with two lipoyl groups at its junction (PEG-L 2 -PCL) showed markedly enhanced stability against dilution, whereas released DOX rapidly in response to 10 mM DTT with about 75% release in 9 h under otherwise the same conditions (87). Wang et al prepared reduction-sensitive SCL micelles from pendant thiol-containing PEG-bpoly(thioethyl ethylene phosphate)-b-PCL (PEG-b-PEEP SH -b-PCL) triblock copolymer followed by oxidative cross-linking in the H 2 O 2 aqueous solution (76). Thus formed SCL micelles revealed enhanced stability against FIG.…”
Section: Reduction-sensitive Reversibly Scl Micelles and Polymersomesmentioning
confidence: 99%